Biocompatibility and antimicrobial activity of biphasic calcium phosphate powders doped with metal ions for regenerative medicine. Issue 17 (1st December 2017) - Marques, Catarina F.; Olhero, Susana; Abrantes, J.C.C.; Marote, Ana; Ferreira, Sónia; Vieira, Sandra I.; Ferreira, José M.F.
Abstract: Biphasic [hydroxyapatite (HA) + β -tricalcium phosphate ( β -TCP)] calcium phosphate powders with partial substitutions of Ca 2+ by silver, copper, zinc and strontium ions were synthesized by precipitation. The aim was to improve the overall biological performance (antimicrobial effect and stimulated osteoblasts proliferation) of the bone graft materials made thereof. The prepared powders were calcined and characterized by different techniques including X-ray diffraction (XRD), elemental analysis, thermo gravimetric and differential thermal analysis (TG-DTA), Fourier Transform Infrared Spectroscopy (FT-IR) and Scanning Electron Microscopy (SEM). Rietveld refinement was used for quantitative phase analysis. The in vitro biocompatibility and the antibacterial activity of the powders were evaluated through the resazurin viability test with MG63 cells, and against Escherichia coli and Staphylococcus aureus, respectively. The quantitative elemental analysis revealed that only strontium ions have been fully incorporated into both HA and β -TCP phases. The in vitro biocompatibility with pre-osteoblastic cells was proved for all synthesized powders, while only the silver-doped powders exhibited antimicrobial activity against S. Aureus . The information gathered is of high relevance for designing improved calcium phosphate bioceramics.